Overexpression of a Cytochrome P450 Monooxygenase Involved in Orobanchol Biosynthesis Increases Susceptibility to Fusarium Head Blight - Changenet, Valentin; Macadré, Catherine; Boutet-Mercey, Stéphanie; Magne, Kévin; Januario, Mélanie; Dalmais, Marion; Bendahmane, Abdelhafid; Mouille, Grégory; Dufresne, Marie (Frontiers in Plant Science, 2021)
Fusarium Head Blight (FHB) is a cereal disease caused primarily by the ascomycete fungus Fusarium graminearum with public health issues due to the production of mycotoxins including deoxynivalenol. Genetic resistance is an efficient protection mean and numerous quantitative trait loci have been identified, some of them related to the production of resistance metabolites. In this study, we have functionally characterized the Brachypodium distachyon BdCYP711A29 gene encoding a cytochrome P450 monooxygenase (CYP). We showed that BdCYP711A29 belongs to an oligogenic family of five members. However, following infection by F. graminearum, BdCYP711A29 is the only copy strongly transcriptionally induced in a deoxynivalenol-dependent manner. The BdCYP711A29 protein is homologous to the Arabidopsis thaliana MAX1 and Oryza sativa MAX1-like CYPs representing key components of the strigolactone biosynthesis. We show that BdCYP711A29 is likely involved in orobanchol biosynthesis. Alteration of the BdCYP711A29 sequence or expression alone does not modify plant architecture, most likely because of functional redundancy with the other copies. B. distachyon lines overexpressing BdCYP711A29 exhibite an increased susceptibility to F. graminearum, although no significant changes in defense gene expression were detected. We demonstrate that both orobanchol and exudates of Bd711A29 overexpressing lines stimulate the germination of F. graminearum macroconidia. We therefore hypothesize that BdCYP711A29 by contributing to orobanchol biosynthesis is a susceptibility factor to FHB.